2014
DOI: 10.1039/c4cp01275e
|View full text |Cite
|
Sign up to set email alerts
|

High energy conformers of M+(APE)(H2O)0–1Ar0–1 clusters revealed by combined IR-PD and DFT-MD anharmonic vibrational spectroscopy

Abstract: IR-PD vibrational spectroscopy and DFT-based molecular dynamics simulations are combined in order to unravel the structures of M(+)(APE)(H2O)0-1 ionic clusters (M = Na, K), where APE (2-amino-1-phenyl ethanol) is commonly used as an analogue for the noradrenaline neurotransmitter. The strength of the synergy between experiments and simulations presented here is that DFT-MD provides anharmonic vibrational spectra that unambiguously help assign the ionic clusters structures. Depending on the interacting cation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…low and higher energy conformers. Experimental and dynamical theoretical spectra including anharmonic vibrational effects 18,52 can furthermore be compared at that stage. This spectroscopic comparison is presented in ref.…”
Section: Discussionmentioning
confidence: 99%
“…low and higher energy conformers. Experimental and dynamical theoretical spectra including anharmonic vibrational effects 18,52 can furthermore be compared at that stage. This spectroscopic comparison is presented in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The effective temperatures of cluster ions can be deduced using RRKM-EE formulism. 53,74 Previous studies have shown that the effective temperatures of cation-biomolecule-water complexes, where water loss is the predominant evaporative cooling mechanism, are B300 K. 24,[45][46][47] Isotopic (H/D) analyses were applied to M + (indole)(H 2 O) 5,6 clusters to facilitate the identification of specific vibrational features and will be discussed in detail in the corresponding sections.…”
Section: Resultsmentioning
confidence: 99%
“…Following the absorption of a single photon, fragmented species are mass selected by a second quadrupole mass filter, tuned to the H 2 O loss channel, and detected by a Channeltron electron multiplier detector in pulse mode. The OPO/OPA laser scans through the OH/NH (3300 cm À1 to 3800 cm À1 ) and OD (2350 cm À1 to 2850 cm À1 ) stretching frequency regions at a step of 3 cm À1 (the typical Full Width Half Maximum, FWHM, of the vibrational spectral features are more than 15 cm À1 in our experimental set-up 24,46,47,75 ). Absolute frequencies are determined by calibration with known water absorption lines that are simultaneously detected photoacoustically and recorded with the IRPD spectrum.…”
Section: Computational and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such strategies can be found in e.g. refs , , , and for various gas-phase molecular systems. Exploring and localizing minima on the PES are nowadays a routine performed by all well-known classical MD and quantum chemistry packages (e.g., GROMACS, LAMMPS, Schrodinger suite, Gaussian, TURBOMOLE, ADF, Gamess, NWChem, ORCA, and for most other popular packages used in the gas-phase community).…”
Section: Theoretical Approachesmentioning
confidence: 99%